2018
DOI: 10.1007/s10103-018-02699-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy for the treatment of androgenetic alopecia in Thai men and women: a 24-week, randomized, double-blind, sham device-controlled trial

Abstract: Low-level laser/light therapy (LLLT) has been increasingly used for promoting hair growth in androgenetic alopecia (AGA). Our institute developed a new home-use LLLT device, RAMACAP, with optimal penetrating energy, aiming to improve therapeutic efficacy and compliance. To evaluate the efficacy and safety of the new helmet-type LLLT device in the treatment of AGA, a 24week, prospective, randomized, double-blind, sham device-controlled clinical trial was conducted. Forty subjects with AGA (20 men and 20 women) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(75 citation statements)
references
References 28 publications
(48 reference statements)
2
73
0
Order By: Relevance
“…The ability of LLLT to induce vasodilation and increase blood flow has also been reported 40 . It has been confirmed in several placebo‐control trials for therapeutic effects and safety 41‐43 . Esmat et al reported hair regrowth at a deeper dermal level in combination therapy compared to monotherapy, thus inducing hair follicles to anchor more firmly with probable higher sustainability 30 .…”
Section: Discussionmentioning
confidence: 88%
“…The ability of LLLT to induce vasodilation and increase blood flow has also been reported 40 . It has been confirmed in several placebo‐control trials for therapeutic effects and safety 41‐43 . Esmat et al reported hair regrowth at a deeper dermal level in combination therapy compared to monotherapy, thus inducing hair follicles to anchor more firmly with probable higher sustainability 30 .…”
Section: Discussionmentioning
confidence: 88%
“…Suchonwanit et al [26] described the use of the RAMACAP helmet-type LLLT device for treating AGA and FPHL. In this randomized, double-blinded, sham device-controlled study, 36 total subjects including both female patients with Ludwig-Savin Baldness score I–III and male patients with Norwood-Hamilton Baldness scores III–V were treated with either the RAMACAP helmet-type LLLT device or a sham device (10 men and 10 women in each group).…”
Section: Resultsmentioning
confidence: 99%
“…The treatment with the RAMACAP helmet-type LLLT device resulted in no adverse events, discontinuation, or interruption of the study. Overall, Suchonwanit et al [26] proposed that the RAMACAP helmet-type LLLT device demonstrated the ability to safely improve AGA and FPHL by increasing terminal hair counts and hair diameter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Other treatment options currently available include low-level laser therapy, fractional laser therapy, platelet-rich plasma, human follicle stem cells and hair transplantation. [8][9][10][11][12] Nevertheless, the treatment outcome may not be satisfactory in some patients. Finasteride, an inhibitor of type II 5α-reductase enzyme, is currently indicated for AGA in men.…”
Section: Introductionmentioning
confidence: 99%